Emotional Intelligence is Related to Adolescent Knowledge About the Dangers of Pregnancy at a Young Age - Eka Fitri Amir; Murniati Safitri; Masriani Situmorang (UIMA Press, 2021)
Background: Adolescent knowledge is influenced by internal factors and external factors, Internal factors consist of physical factors and psychological factors. IntellectualIncome (IQ) only accounts for 20% of success and 80% due to other factors. Intelligence plays a very important role in a person's success, one of which is emotional Qoutient (EQ). The results of the interview with 10 responders with the results of 5 people among them could not restrain their emotions and were unable to accept the input of others. If adolescents have a correct and accurate understanding of sexual reproductive health information, the adolescents tend to have a lower risk. Objectives: This study aims to determine the relationship between Emotional Intelligence and adolescent knowledge about the dangers of pregnancy at a young age. Methods: A correlational descriptive type of research with a cross-sectional approach. sampling using random sampling and obtained a total sample of 72 respondents. Data analysis using Kendall Tau. Most of the respondents had moderate emotional intelligence of 48 people (68.6%), and most of the respondents had knowledge in the Good category of 41 people (58.6%). Results: Based on a statistical analysis test using Kendall Tau between emotional intelligence and adolescent knowledge about the dangers of pregnancy at a young age, a value of (τ) of 0.508 was obtained. Conclusion: Then it can be concluded There is a significant relationship between emotional intelligence and with adolescent knowledge of the dangers of pregnancy at a young age.